Occupational health professionals’ knowledge, understanding and use of work ability - Coomer, K.; Houdmont, Jonathan (Oxford Journals, 2013)
BACKGROUND: The concept of work ability (WA) has a 30-year history in Finland, where it has been used extensively in occupational health (OH) research and practice. The extent to which WA has been integrated into UK OH practice is unclear. AIMS: (i) To compare knowledge, understanding and use of WA among OH nurses and physicians in the UK and Finland and (ii) to identify factors that influence the use of WA in Finnish OH practice. METHODS: An online questionnaire administered to OH practitioners in the UK and Finland. RESULTS: A total of 436 UK and 97 Finnish OH practitioners completed the questionnaire. Though familiarity with the term 'work ability' was similar among Finnish and UK respondents, substantial differences were found in understanding of the term. Ninety-five per cent (Finland) and 7% (UK) of respondents reported using the Work Ability Index (WAI), a validated measure of WA, in their practice. Finnish respondents indicated that they used the WAI results primarily for individual case management, understanding population health trends, health promotion and determining WA across age groups. UK respondents primarily attributed failure to use the WAI to lack of training. Primary factors influencing use of WA in Finland included it being considered common practice and an effect ive system by which to conduct individual assessments. CONCLUSIONS: There are large differences between Finland and the UK in the assessment of WA in OH practice. Differences may reflect contrasting OH legislative frameworks.